Corrosion failure analysis and microstructure characterization of emulsion on hydraulic cylinder base. Issue 1 (July 2021) - Zhiwei, Zhang; Fan, Wang; Sufen, Liu; Hongwei, Zhou; Wenyuan, Geng; Zhaojie, Li
Abstract: This paper studies the corrosion of the base of the 30CrMnSi hydraulic cylinder due to changes in emulsion concentration during maintenance and its effect on alloy performance. The results show that the corrosion characteristics of the base of the hydraulic cylinder are comprehensive corrosion and local point corrosion, and that the anti-rust performance of emulsion in contact with the outer surface of the hydraulic cylinder base is insufficient, and the chemical reaction with its surface is the main cause of the corrosion of the components. According to the analysis, the hydraulic cylinder base can not be stored at a reasonable emulsion concentration, resulting in a decrease in its surface pitting potential, so that its ability to cope with environmental corrosion decreased, after a period of time, rust on its surface.